SkipNet: A Scalable Overlay Network with Practical Locality Properties - Harvey, Nicholas J.A.; Dunagan, John; Jones, Mike; Saroiu, Stefan; Theimer, Marvin; Wolman, Alec (2002)
Scalable overlay networks such as Chord, CAN, Pastry, and Tapestry have recently emerged as flexible infrastructure for building large peer-to-peer systems. In practice, such systems have two disadvantages: They provide no control over where data is stored and no guarantee that routing paths remain within an administrative domain whenever possible. SkipNet is a scalable overlay network that provides controlled data placement and guaranteed routing locality by organizing data primarily by string names. SkipNet allows for both fine-grained and coarse-grained control over data placement: Content can be placed either on a pre-determined node or distributed uniformly across the nodes of a hierarchical naming subtree. An additional useful consequence of SkipNet’s locality properties is that partition failures, in which an entire organization disconnects from the rest of the system, can result in two disjoint, but well-connected overlay networks. Furthermore, SkipNet can efficiently re-merge these disjoint networks when the partition heals.
Note: The technical report previously numbered MSR-TR-2002-92, "A Polynomial-time Rescaling Algorithm for Solving Linear Programs," is now numbered MSR-TR-2003-09.